The socio-territorial belonging in a cross-border area: a sociological approach. Issue 2 (3rd May 2016) - Pretto, Albertina; Battello, Veronica
Abstract : This paper presents a case study carried out in the Italian town of Gorizia and the Slovenian town of Nova Gorica. These two towns used to belong to the same nation, whereas now they are separated by a national border. Since their separation, their history and social processes have taken different paths, but the two towns are located along the same border area. The research focuses on the sense of socio-territorial belonging in the Gorizia and Nova Gorica residents towards their respective town, country and Europe. A particular type of qualitative interview with photos was applied: the bipolar photo elicitation.